Strain-induced precipitation behaviors of 7Mo super-austenitic stainless steel - Shiguang Xu; Jinshan He; Runze Zhang; Fucheng Zhang; Xitao Wang (Journal of Materials Research and Technology, 2023)
Strain-induced precipitation (SIP) behaviors of 7Mo super-austenitic stainless steel (SASS) were studied by strain relaxation test at 850 °C. Our results reveal that sigma (σ) phases are the predominant SIP of 7Mo SASS, with the chemical formula of (FeNi) (CrMo). SIP first precipitates in granular shape at HAGBs, such as deformed grain boundaries (SIP-GBs), interfaces between deformation twin layers and matrix (SIP-TW), and HAGBs inside deformed grains (SIP-HAGBs). This is attributed to the ability of HAGBs for providing high deformation stored energy, nucleation sites, and efficient element diffusion channels. When the nucleation sites at HAGBs become saturated with increasing holding time, needle-like SIPs (SIP-NL) are precipitated along closely packed planes of γ-Fe matrix. The specific orientation relationships between SIP-NL and matrix, namely (−111)γ-Fe//(00–1)σ, [0–11]γ-Fe//[-110]σ or (-1-1-1)γ-Fe//(00–1)σ, [0–11]γ-Fe//[-110]σ, and the needle-like shape are contribute to minimizing interfacial energy and elastic strain energy of SIP, respectively, thereby promoting SIP-NL. The absence of SIP on dislocations can be attributed to the large critical nucleus size of σ phase (about 4.87 nm), which poses challenges for SIP nucleation through dislocation distortion energy. Mo is the controlling element for the nucleation and growth of SIP. SIP can promote cDRX through particle-induced nucleation (PSN) mechanism during the deformation process, while residual high-density dislocations around SIP can also promote cSRX during the holding process. During holding process, the boundaries of recrystallized grains can also serve as nucleation sites for SIP, thereby promoting SIP, and finally form a multi-layer structure of “σ phase/Recrystallization/σ phase”.